The effect of jump direction and planning on drop landing mechanics in female athletes - King, A. C.; Day, B.; Patton, J.; Turner, S.; Wright, E.; Bird, M. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to assess differences in landing and jump kinematics during a drop landing task in female athletes. Participants (n=18) with previous athletic experience (i.e., jumping sports) volunteered for the study and performed planned and unplanned jumps in three different directions (left, straight, right). Kinematic and kinetic data were analyzed from initial ground contact and toe off. Preferential weight distribution toward the right side was found during the bilateral drop landing task which was supported by larger peak ground reaction forces (GRFPeak)on the right limb. Jump direction significantly altered total plate time (p<0.05), GRFPeak (p<0.001), mean GRF symmetry (p< 0.01), and knee path distance (p<0.05). Based on these findings, off-center jumps, but not anticipation, altered landing and jumping kinematics in a manner that may relate to knee injury risk.